Synovial fluid fibrin degradation product can be used as a new auxiliary marker for periprosthetic joint infection diagnosis - Huang, Jincheng; Chen, Peng; Zhang, Zhaodong; Cheng, Cheng; Peng, Puji; Li, Yunfei; Meng, Dongfang; Liu, Tao; Jin, Yi (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundWhile the value of blood coagulation markers, such as D-Dimer, Fibrinogen, platelet count/mean platelet volume ratio (PC/MPV), and Fibrin Degradation Product (FDP), in the diagnosis of periprosthetic joint infection (PJI) has been explored in recent years, the significance of synovial fluid coagulation markers in PJI diagnosis remains unclear. Therefore, this study aims to investigate the potential value of synovial fluid D-Dimer (sD-Dimer) and synovial fluid FDP (sFDP) in the diagnosis of PJI.Materials and methodsIn a prospective study, the levels of serum C-reactive Protein (CRP), Erythrocyte Sedimentation Rate (ESR), sD-Dimer, and sFDP were measured and compared in 56 patients with PJI (Group A) and 40 patients with aseptic loosening (Group B) who presented at our department from March 1st, 2020, to December 31st, 2023. The diagnostic efficacy of these markers in PJI diagnosis was assessed using the area under the curve (AUC) of the receiver operating characteristic (ROC) curve.ResultsThe levels of CRP, ESR, sD-Dimer, and sFDP in Group A were significantly higher than the levels in Group B. The AUC values, optimal threshold values, sensitivity, and specificity for CRP, ESR, sD-Dimer, and sFDP in PJI diagnosis were as follows: CRP [0.920 (95% confidence interval (CI), 0.846–0.965), >6.77, 76.69%, 95.00%], ESR [0.905 (95% CI, 0.828–0.955), >41, 73.21%, 92.50%], sD-Dimer [0.788 (95% CI, 0.692–0.864), >738.65, 66.07%, 80.00%], and sFDP [0.869 (95% CI, 0.785–0.929), >1558.35, 91.07%, 70.00%]. Furthermore, sFDP demonstrated similar performance in PJI diagnosis to CRP and ESR, while sD-Dimer exhibited inferior performance in PJI diagnosis compared to CRP and ESR.ConclusionssFDP shows promise as a valuable new adjunctive diagnostic marker for PJI. Further investigations with larger sample sizes are warranted.